Effects of the volatile anesthetic sevoflurane on tonic GABA currents in the mouse striatum during postnatal development. (19th August 2014) - Ando, Nozomi; Sugasawa, Yusuke; Inoue, Ritsuko; Aosaki, Toshihiko; Miura, Masami; Nishimura, Kinya
Abstract The volatile anesthetic sevoflurane, which is widely used in pediatric surgery, has proposed effects on GABAA receptor‐mediated extrasynaptic tonic inhibition. In the developing striatum, medium‐sized spiny projection neurons have tonic GABA currents, which function in the excitatory/inhibitory balance and maturation of striatal neural circuits. In this study, we examined the effects of sevoflurane on the tonic GABA currents of medium spiny neurons in developing striatal slices. Sevoflurane strongly increased GABAA receptor‐mediated tonic conductance at postnatal days 3–35. The antagonist of the GABA transporter‐1, 1‐[2‐[[(diphenylmethylene)imino]oxy]ethyl]‐1, 2, 5, 6‐tetrahydro‐3‐pyridinecarboxylic acid hydrochloride further increased tonic GABA conductance during the application of sevoflurane, thereby increasing the total magnitude of tonic currents. Both GABA (5 μm) and 4, 5, 6, 7‐tetrahydroisoxazolo[5, 4‐c]pyridine‐3‐ol hydrochloride, the δ‐subunit‐containing GABAA receptor agonist, induced tonic GABA currents in medium spiny neurons but not in cholinergic neurons. However, sevoflurane additively potentiated the tonic GABA currents in both cells. Interestingly, 4, 5, 6, 7‐tetrahydroisoxazolo[5, 4‐c]pyridine‐3‐ol hydrochloride‐sensitive neurons made a large current response to sevoflurane, indicating the contribution of the δ‐subunit on sevoflurane‐enhanced tonic GABA currents. Our findings suggest that sevoflurane can affect the tone of tonic GABA inhibition in a developing striatal neural network.